The minor myosin heavy chain, mhcA, of Caenorhabditis elegans is necessary for the initiation of thick filament assembly. - Waterston, R H (1989)
Caenorhabditis elegans body wall muscle has two distinct myosin heavy chain isoforms, mhcA and mhcB. Mutations eliminating the major isoform, mhcB, have previously been shown to yield paralyzed, viable animals. In this paper we show that the minor isoform, mhcA, is essential for viability. We have utilized the known physical map position of the gene encoding mhcA to obtain two recessive lethal mutations that virtually eliminate accumulation of mhcA. The mutations are allelic, and the interactions of these alleles with mutations affecting other thick filament components are consistent with the hypothesis that the new mutations lie in the structural gene for mhcA. The homozygous mutant animals move very little and morphological analysis shows that thick filament assembly is severely impaired. Together with the location of mhcA in the center of the thick filament (Miller et al., 1983), the results suggest that mhcA has a unique role in initiating filament assembly. The homozygous mutations have an unexpected effect on morphogenesis that indicates an interaction between the muscle cells and the hypodermis during development. The resultant phenotype may be useful in the search for additional essential muscle genes.